Does bilateral seminal vesicle invasion at radical prostatectomy predict worse prognosis than unilateral invasion among patients with pT3b prostate cancers?. (16th June 2016) - Lee, Hyun Jung; Han, Jun‐Hee; Lee, Dong Hoon; Nam, Jong Kil; Kim, Tae Nam; Chung, Moon Kee; Park, Sung‐Woo
Abstract : Objectives: To determine whether bilateral seminal vesicle invasion is associated with worse biochemical recurrence‐free survival than unilateral seminal vesicle invasion after radical prostatectomy. Methods: We reviewed the clinicopathological data of 598 men who underwent radical prostatectomy between 2008 and 2015. Among them, 107 (17.9%) had seminal vesicle invasion. After excluding cases with neo‐/adjuvant hormone treatment or radiotherapy, 93 were included in the analysis. We compared biochemical recurrence‐free survival rates in subgroups with or without bilateral seminal vesicle invasion using Kaplan–Meier estimates. Cox proportional hazard regression models were used to determine the predictors of biochemical recurrence‐free survival. Results: Bilateral prostatic lobes and bilateral seminal vesicles were involved by prostate cancers in 85 (91.4%) and 35 patients (37.6%), respectively. Actuarial 3‐year and 5‐year biochemical recurrence‐free survival rates in patients with pT3b tumors with/without bilateral seminal vesicle invasion were 13.0%/34.3%, and 4.3%/19.8%, respectively. On multivariable analysis, preoperative prostate‐specific antigen (hazard ratio 1.01, 95% confidence interval 1.00–1.02, P = 0.034), lymph node metastasis (hazard ratio 2.88, 95% confidence interval 1.43–5.81, P = 0.003) and bilateral seminal vesicle invasion (hazard ratio 1.75, 95% confidence interval 1.01–3.05, P = 0.047) were independent predictors of biochemical recurrence‐free survival. After excluding cases with lymph node metastasis, preoperative prostate‐specific antigen, surgical margin status and bilateral seminal vesicle invasion were independent predictors of biochemical recurrence‐free survival. Conclusions: Although most men with seminal vesicle invasion experience biochemical recurrences after radical prostatectomy, their survival outcome is not uniform. Bilateral seminal vesicle invasion seems to represent an independent prognostic factor for pT3b patients, together with the preoperative prostate‐specific antigen and lymph node status.